The effects of pregnancy discrimination on postpartum depressive symptoms: a follow-up study - Yuko Kachi; Takeo Fujiwara; Akiomi Inoue; Sachiko Baba; Hisashi Eguchi; Hiroshi Ohta; Akizumi Tsutsumi (BMC, 2022)
Abstract Background Pregnancy discrimination in the workplace is prevalent worldwide. However, few studies have examined the effects of pregnancy discrimination on mothers' perinatal mental health. We aimed to investigate the association between pregnancy discrimination and postpartum depressive symptoms, and the mediation effects of prenatal depressive symptoms on this association. Methods Our sample consisted of 285 Japanese women employed during pregnancy who completed a baseline online survey in May 2020 and a follow-up mail survey two months postpartum. Pregnancy discrimination was defined as exposure to any of 16 forms of disadvantageous treatment or harassment related to pregnancy, prohibited by national guidelines. Prenatal (assessed at baseline) and postpartum (assessed at follow-up) depressive symptoms were measured using the Edinburgh Postnatal Depression Scale. Multiple linear regression and mediation analyses were performed overall and stratified by regular (permanent) and non-regular (precarious) employees. Results Overall, 23.9% of participants experienced pregnancy discrimination during pregnancy. After adjusting for potential confounders, pregnancy discrimination was significantly associated with postpartum depressive symptoms (coefficient 1.76, 95% confidence interval [CI] 0.65-2.88). When stratified by employment type, these effects were observable among non-regular employees (coefficient 2.51, 95% CI 0.45-4.57) but not regular employees. Mediation analysis showed that prenatal depressive symptoms mediated 57.1% (95% CI 20.1-94.1%) of the association between pregnancy discrimination and postpartum depressive symptoms among all participants, with a greater effect among non-regular employees (64.1% [95% CI 18.5-109.8%]). Conclusions Pregnancy discrimination has adverse effects on postpartum depressive symptoms, partially through prenatal depressive symptoms, especially among non-regular employees. To prevent perinatal depression in female workers, employers should comply with legislation and take preventive measures against pregnancy discrimination, while considering vulnerable employees.